CONDIÇÕES DE VIDA: TRABALHO, SAÚDE E ALIMENTAÇÃO DE CATADORES DE MATERIAL RECICLÁVEL NA REGIÃO METROPOLITANA DE CURITIBA - Julieanne Reid Arcain; Marcia Oliveira Lopes; Silvia do Amaral Rigon; Milene Zanoni da Silva (Universidade do Estado do Rio de Janeiro, 2018)
Introduction: Recyclable waste pickers, despite being essential professionals for the socio-environmental development of municipalities, form a socially vulnerable group. Thus, for health promotion actions, it is necessary to understand the health / disease process in these groups, locally knowing the influence of social, economic and cultural determinants. Objective: To characterize the health, food and working conditions of collectors of recyclable material of an association in the metropolitan region of Curitiba. Methodology: The study used a descriptive, exploratory and qualitative approach. The food condition was analyzed by the Brazilian Food Insecurity Scale. The action-research was used, starting from the analysis of the characterization data of the group. The contents that emerged in the group were elaborated in workshops with the use of the Arch of Maguerez. Results and Discussions: In a group of 11 participants, nine women and two men, only two respondents presented a food security situation, four were under mild food insecurity and six, under moderate food insecurity. It was noticed that the health of these workers is directly affected by the working and feeding conditions, which in turn are related to an insufficient level of income and to low schooling level. The workshops were an opportunity for the collective construction of knowledge related to health, starting from the demands of those involved. Conclusion: Self- care presented itself as a question to be addressed as a priority by the group. The reflections and actions resulting from the dynamics of the research collaborated to an increase in the empowerment of the group that showed interest in moving forward in this process, especially in what concerns the search for their rights. DOI: 10.12957/demetra.2018.37509